CONDITIONS OF FORMATION OF GAGARINITE, AS SHOWN BY THE STUDY OF FLUID INCLUSIONS - Prokof'yev V.Y.; Ryabenko S.V. (My University, 1988)
A rare-earth fluoride of sodium and calcium with the formula NaCaREF6 was discovered in 1958 in an albitized granite (apogranite) pluton and called gagarinite. It is a typomorphic mineral of rare-metal alkalic metasomatites, enriched in fluorine and formed from granites relatively high in alkalies, as well as from metamorphic rocks. While studying the conditions of formation of fluorides from a cryolite-rare metal deposit in eastern Siberia, the present writers for the first time found and studied individual fluid inclusions in gagarinite. This deposit is near the junction of Lower Proterozoic geosynclinal fold structures with the Archean fractured and downfaulted, pericratonic basement. Gagarinite mineralization in metasomatic rocks occurs as accessory disseminations and, less commonly, as veinlets and pockets. Study results suggest that gagarinite crystallized from high-temperature fluoride-chloride hydrothermal solutions, in which sodium evidently predominated to a considerable extent over calcium. Such solutions usually also deposit cryolite commonly associated with gagarinite.
Keywords: Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Архей; Precambrian::Archean; Докембрий::Протерозой